Microbiome-based solutions to address new and existing threats to food security, nutrition, health and agrifood systems' sustainability - Callens, Karel; Fontaine, Fanette; Sanz, Yolanda; Bogdanski, Anne; D‘Hondt, Kathleen; Lange, Lene; Smidt, Hauke; van Overbeek, Leo; Kostic, Tanja; Maguin, Emmanuelle; Meisner, Annelein; Sarand, Inga; et al. (Frontiers in Sustainable Food Systems, 2022)
In addition to challenges like climate change and biodiversity loss, the sustainability and resilience of agrifood systems worldwide are currently challenged by new threats, such as the COVID-19 pandemic and the Ukraine war. Furthermore, the resilience and sustainability of our agrifood systems need to be enhanced in ways that simultaneously increase agricultural production, decrease post-harvest food losses and food waste, protect the climate, environment and health, and preserve biodiversity. The precarious situation of agrifood systems is also illustrated by the fact that overall, around 3 billion people worldwide still do not have regular access to a healthy diet. This results in various forms of malnutrition, as well as increasing number of people suffering from overweight and obesity, and diet-related, non-communicable diseases (NCDs) around the world. Findings from microbiome research have shown that the human gut microbiome plays a key role in nutrition and diet-related diseases and thus human health. Furthermore, the microbiome of soils, plants, and animals play an equally important role in environmental health and agricultural production. Upcoming, microbiome-based solutions hold great potential for more resilient, sustainable, and productive agrifood systems and open avenues toward preventive health management. Microbiome-based solutions will also be key to make better use of natural resources and increase the resilience of agrifood systems to future emerging and already-known crises. To realize the promises of microbiome science and innovation, there is a need to invest in enhancing the role of microbiomes in agrifood systems in a holistic One Health approach and to accelerate knowledge translation and implementation.